Theories of Attention in Domestic and Western Psychology - Tokhniyazov, R. R.; Kamzanova, A. Т. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2018)
The question of the attention nature is the one of the most important in modern psychology. Theoretical dissociation does not allow researchers to effectively move in the study of this mental phenomenon. Modern researchers use a variety of tools based on different theoretical approaches and therefore, their results cannot be brought together for general analysis. This problem complicates applying opportunities of these studies. The aim of this work was to analyze and present theories of attention in Western and domestic psychology. Through this analysis of the theoretical path, we can assume the next step in the development of understanding of attention. The theoretical review is made in chronological order with the block of the Western psychologist’s theories review and then the domestic psychologist’s theories review. The review presents the theories of the following Western psychologists: William James, Wilhelm Wundt, Edward Titchener, Edgar Rubin, Kurt Koffka, Wolfgang Kohler, Donald Broadbent, Ulric Neisser, Daniel Kahneman, Michael Posner, Richard Shiffrin, Donald Norman, Tim Shallice, Alan Allport, Odmar Neumann. Theories of domestic psychologists are presented by the following authors: Nikolay Lange, Nikolay Dobrynin, Nikolai Bernstein, Pyotr Galperin, Pyotr Zinchenko, Dimitri Uznadze, Alexey Leontiev, Yuliya Gippenreyter, Yuri Dormashev. As a result of the theoretical review, a considerable dissociation of the researchers was revealed concerning the essence and nature of attention. The work is valuable for those who have begun to study attention, because it gives an overview of all approaches to the issue of attention. In addition, thoughtful and consistent analysis of the existing theories of attention can lead researcher to create a new, unified theory of attention, which will be able to unite the divided camps of different psychological approaches. Key words: attention, attention theories, attention conceptions.